Revisiting KH Muafi Ali Zaini’s Legacy: ‘Modernization’ of Islamic Boarding School in Sampang Madura - Mohammad Thoyyib Madani; Rifki Rufaida; Fauzan Zenrif; Ahmad Barizi; Abd Haris; Zainuddin Zainuddin (Universitas Darussalam Gontor, 2024)
This study examines the modernization movement of Islamic boarding school education led by KH. Muafi Alif Zaini in Sampang, Madura, and its impact on the educational, social, political, and economic life of the surrounding community. Using a qualitative research method with a historical and sociological approach, data were collected through interviews, observations, and documentation involving boarding school leaders, teachers, students, alumni, and community figures. The findings reveal that KH. Muafi Alif Zaini implemented a visionary and spiritual leadership model by integrating religious education with general sciences and practical skills, while maintaining the traditional values of Islamic boarding schools. His modernization efforts transformed the Nazhatut Thullab Islamic Boarding School into a more adaptive and progressive institution through the establishment of formal educational institutions, economic cooperatives, and community empowerment programs. Despite facing strong social resistance due to his political involvement with the Golkar Party, KH. Muafi Alif Zaini remained committed to educational and social transformation. The study concludes that his modernization movement successfully enhanced the image of Islamic boarding schools, strengthened public trust, and contributed significantly to local educational and economic development in Sampang Madura.